The Effect Of Specialized Exercises Based On Gradual Activity Levels in Visual Tracking And The Learning Of Setting And Serve Reception Skills in Volleyball - Amer Rashid Shayyal AL-Zubaidi (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Background. There exists an abundance of information that can be utilized in the learning process across various dimensions, the purpose of which is to identify learners’ individual attributes and abilities. Objectives .The aim of this study was to investigate the effect of specialized exercises based on gradual activity levels on visual tracking, as well as to examine their impact on learning the skills of setting and serve reception in volleyball. The research hypothesized that there would be statistically significant differences in visual tracking ability and in the learning of setting and serve reception skills in volleyball. Materials and Methods. The researcher adopted the experimental method using a two-group design (experimental and control) with pre- and post-tests, as it was appropriate to the nature of the study. The research community and sample consisted of second-year students from the College of Physical Education and Sports Sciences at the University of Wasit for the academic year 2024-2025, with a total sample of 28 students. The two research groups (control and experimental) were randomly assigned in accordance with the suitable conditions for implementing the current study procedures. Results. After conducting the pre-tests, the instructional program was implemented over eight educational units, with each session lasting 90 minutes .Upon completion of the program, post-tests were conducted. Conclusions. The researcher concluded several findings, the most important of which was that students who achieved greater improvement in visual tracking demonstrated better skill acquisition in both setting and serve reception. Among the key recommendations was the need to utilize the instructional program applied in this study for effectively teaching students these volleyball skills.